2018
DOI: 10.3889/oamjms.2018.126
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Effects in Gait Speed in Patients with Knee Osteoarthritis

Abstract: BACKGROUND:Knee osteoarthritis is a chronic degenerative disease, known as the most common cause of difficulty walking in older adults and subsequently is associated with slow walking. Also one of the main symptoms is a degenerative and mechanics type of pain. Pain is very noticeable while walking in rugged terrain, during ascent and descent of stairs, when changing from sitting to standing position as well as staying in one position for a long time. Many studies have shown that the strength of the quadriceps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…We already know that a slower walking speed is associated with incident knee OA and that decreasing walking speed has been suggested as one of the mechanisms to reduce pain in the knee [ 45 ]. However, according to previous studies, walking speed can be increased through specific exercise therapy programs or physiotherapy to improve the muscles around the knee joint [ 46 , 47 ]; our result is in agreement with the results of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…We already know that a slower walking speed is associated with incident knee OA and that decreasing walking speed has been suggested as one of the mechanisms to reduce pain in the knee [ 45 ]. However, according to previous studies, walking speed can be increased through specific exercise therapy programs or physiotherapy to improve the muscles around the knee joint [ 46 , 47 ]; our result is in agreement with the results of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that individuals with HKOA walk slower than healthy controls of the same age. Thus, our results for the top 1 feature agree with the results of prior research[53,115].•Employing the top 3 STPG features extracted from HOA and HC data achieved a mean accuracy (83.67% with SVM) closer by ∼3% to using all 21 STGP features (86.79% with DT). • KNN performance improved by ∼4%, with the top five features outperforming using all STPGs for KOA and HC data.…”
supporting
confidence: 88%
“…The initial 2 metre served to reach a constant speed. The final 2 metre prevented the participant from decelerating prematurely (Juhakoski et al 2008 ; Tani et al 2018 ) ( Appendix 2 ).…”
Section: Methodsmentioning
confidence: 99%